Message - Benatoui , Dr. Rima (Universal Journal of Pharmaceutical Research, 2022)
I salute all the UJPR team, Most researchers challenge all difficulties as: originality of works, materials, meticulous methods, software’s. Keeping along between different teams of researchers is the main cause of enhancing in the high details of one topic discussing in coherence its physiological, cellular, and molecular interaction side, but we sorry for the segregation that often occurs in the same team. Then, fidelity of some authors “treating the same topic” to the journal facilitate to lecturers to pursue their profound research and/or preparation of their pedagogic document. Indexing in Scopus/Thomson Reuters does not mean to some authors, which feels the strictness and accuracy in reviewing process of non-indexed journals whose gives them more confidence between authors and editors. Browsing in previous issues of the journal confirm the careful choice of high proficiency articles by the Editor-in-chief, then their destination to the appropriate reviewer from all over the world. As previous author, services offered by UJPR to authors crown their efforts and accentuate their work path, a sever peer-review system and both the reviewers and author remain anonymous throughout the process. Researchers preferred only a rapid journal, and cited indexed journals in Scopus and publish their articles in non-indexed journals; led some Editors to demand citing publications from previous issues to enhance merits of journal, mostly, with time authors will trust to journals according to other criteria. Researchers should deal with some laws, but fall into the trap of predatory reviews with attractive website, supposedly indexed in Scopus, all this torture distorts the art of research, and its main goal of interchange of information, as delaying its application in industries or hospitals.